DEVELOPMENT THE MODEL OF IMPROVING THE QUALITY OF TRAINING - A. Panychev (Вестник университета, 2017)
Developed the model of improving the training of specialists on the basis of accounting processes of improvement of qualification specialist and formation of its competences in extracurricular process. The final list of competencies formed into the model of professional portrait of specialist (PPS). There were systematized and developed methods for assessing competencies of specialists. In particular was proposed: the algorithm for comparative evaluation of specialists based proximity measure its actual set of competencies to the standard of PPS, the mathematical model to describe the growth of competences.